Struktur Kepemilikan Dan Struktur Dewan Perusahaan - Ella Budiarti; Chorry Sulistyowati (Universitas Airlangga, 2014)
This study aims to determine the effect of ownership structure and corporate board structure. This study use two-tiers board system and use secondary data from non-financial firm which fulfill the requirement and listing in Indonesia Stock Exchange from 2010-2013. The analysis technique used a quantitative method with multiple linear regression. The object of research used in this research are non financial companies listed on the Stock Exchange in 2010 to 2013 the number of samples obtained some 191 samples. The results obtained are foreign ownership and managerial ownership negative significant with board size. And managerial dan government ownership negative significant with independent commissioners but foreign ownership has positive significant. The results emphasize that different ownership has behavior and preferences for corporate governance practices especially board structures.